MATRIX CONVERTER TECHNOLOGY: A REVIEW PAPER - Pratiksha M. Koli; H. T. Jadhav (International Journal of Innovations in Engineering Research and Technology, 2021)
an array of m*n bidirectional power switches is directly connected to the m-phase soures and n-phase load is referred as a matrix converter.